Improving the Delivery of Health Services : A Guide to Choosing Strategies - Berman, Peter; Pallas, Sarah; Smith, Amy L.; Curry, Leslie; Bradley, Elizabeth H. (World Bank, Washington, DC, 2013)
Sufficient funding and efficacious technology may be necessary conditions for achieving health gains, but experience in many countries confirms that they are not sufficient. Effective and efficient service delivery is the point at which the potential of the health system to improve lives meets the opportunity to realize health gains. Health service delivery performance means access and use by those in need; adequate quality of care to produce health benefits; efficient use of scarce resources; and organizations that can learn, adapt, and improve for the future. All too often, potential benefits are not realized because service delivery underperforms. Organizations must combine financial, physical, and human resources to deliver health services. However, organizations can be complex, and this complexity must be considered in developing strategies for change. This guide will help planners and policy makers navigate the complexity and make better decisions to improve health services. Users of this Guide will find practical advice about what performance means in service delivery as well as how to measure the performance of service delivery organizations. The Guide discusses reforms to service delivery organizations at the system level and at the individual facility level. It emphasizes the internal workings of the organization as well as the external environment in which an organization functions, and discusses its capacity to develop and manage change. A diverse set of theories and concepts explaining organization performance are brought together and compared. Guidance is given on how to identify the root causes of poor performance, the most plausible explanations underlying these causes, and the right strategies to address and improve performance.